A Compendium of Preparation and Application of Stem Cells in Parkinson's Disease: Current Status and Future Prospects - Shen, Yan; Huang, Jinsha; Liu, Ling; Xu, Xiaoyun; Han, Chao; Zhang, Guoxin; Jiang, Haiyang; Li, Jie; Lin, Zhicheng; Xiong, Nian; Wang, Tao (Frontiers in Aging Neuroscience, 2016)
Parkinson's Disease (PD) is a progressively neurodegenerative disorder, implicitly characterized by a stepwise loss of dopaminergic (DA) neurons in the substantia nigra pars compacta (SNpc) and explicitly marked by bradykinesia, rigidity, resting tremor and postural instability. Currently, therapeutic approaches available are mainly palliative strategies, including L-3,4-dihydroxy-phenylalanine (L-DOPA) replacement therapy, DA receptor agonist and deep brain stimulation (DBS) procedures. As the disease proceeds, however, the pharmacotherapeutic efficacy is inevitably worn off, worse still, implicated by side effects of motor response oscillations as well as L-DOPA induced dyskinesia (LID). Therefore, the frustrating status above has propeled the shift to cell replacement therapy (CRT), a promising restorative therapy intending to secure a long-lasting relief of patients' symptoms. By far, stem cell lines of multifarious origins have been established, which can be further categorized into embryonic stem cells (ESCs), neural stem cells (NSCs), induced neural stem cells (iNSCs), mesenchymal stem cells (MSCs), and induced pluripotent stem cells (iPSCs). In this review, we intend to present a compendium of preparation and application of multifarious stem cells, especially in relation to PD research and therapy. In addition, the current status, potential challenges and future prospects for practical CRT in PD patients will be elaborated as well.